1985
DOI: 10.3354/meps023129
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of bactivorous grazers and heterotrophic bacteria with dissolved organic matter

Abstract: Ciliated Protozoa (Euplotes sp, and Uronema sp.) and natural microzooplankton assemblages (10 to 200 pm) -collected from Los Angeles Harbor, a coastal lagoon, and San Pedro Channelwere fed bacteria previously labeled with 14C(U)-glucose. Dissolved organic carbon-l4 (D014C) released during grazing was collected and subsequently fractionated by AMICON ultrafiltration into 5 nominal molecular weight (NMW) classes: > 105, 104 to 105, 103 to 104, 5 X 102 to 103, and < 5 X 102 daltons. Release of labeled organic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 28 publications
5
64
0
Order By: Relevance
“…Several of these methods assume that bacterial growth without grazers is similar to growth with grazers, although it has been shown that bacterivorous nanoflagellates release nutrients (Burney et al 1981, Andersson et al 1985, Goldman et al 1985, Giide 1985, Taylor et al 1985 and in turn nurture bacterial production (Sherr et al 1982. Radioisotope techniques suffer from several limitations including artifacts arising from isotopic label leaking into the medium.…”
Section: Introductionmentioning
confidence: 99%
“…Several of these methods assume that bacterial growth without grazers is similar to growth with grazers, although it has been shown that bacterivorous nanoflagellates release nutrients (Burney et al 1981, Andersson et al 1985, Goldman et al 1985, Giide 1985, Taylor et al 1985 and in turn nurture bacterial production (Sherr et al 1982. Radioisotope techniques suffer from several limitations including artifacts arising from isotopic label leaking into the medium.…”
Section: Introductionmentioning
confidence: 99%
“…KDOC was used as the partition coefficient for the remainder of the bacterial cell because I assumed that the bacterial-derived DOC was similar in composition to the non-lipid cellular components within the bacterial cell. This assumption was derived from studies of bacterial-derived and grazer-enhanced DOC which showed that the DOC composition was similar to that of the bacterial cell (Taylor et al, 1985). Using these approximations, KB was calculated to be 10563.…”
Section: Calculation Of Expected and Measured Extraction Rate Constantsmentioning
confidence: 99%
“…The dependence of Kp on organic carbon content and compound hydrophobicity in this model is assumed to be similar to that of Kp in the two-phase model described above. However, it is possible that colloidal material has a different composition than the larger particulate material (e.g., Taylor et al, 1985). As a 16 result, two different Kp's should be used to explain fully the partitioning behavior of PCBs (Gschwend and Wu, 1985).…”
Section: Current Models Of Speciationmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct excretory losses to DOC are probably small (Nagata 2000), e.g. 3 to 9% of intake (Taylor et al 1985). The final mode of zooplankton DOC release, from fecal pellets, has been proposed as an important source (Jumars et al 1989, Lampitt et al 1990, Nagata 2000, with as much as 50% of C in pellets being rapidly solubilized (Urban-Rich 1999).…”
mentioning
confidence: 99%